A Critical Role for the Mitochondrial Pyruvate Carrier in Hepatic Stellate Cell ActivationSummary - Mohammad Habibi; Daniel Ferguson; Sophie J. Eichler; Mandy M. Chan; Christina Fu; Terri A. Pietka; Andrea L. Bredemeyer; Andrew LaPoint; Trevor M. Shew; Mai He; Kim H.H. Liss; Andrew J. Lutkewitte; et al. (Cellular and Molecular Gastroenterology and Hepatology)
Background & Aims: Hepatic stellate cells (HSCs) are non-parenchymal cells of the liver that produce the extracellular matrix that forms fibrotic lesions in chronic liver disease, including metabolic dysfunction-associated steatohepatitis (MASH). The mitochondrial pyruvate carrier (MPC) catalyzes the transport of pyruvate from the cytosol into the mitochondrial matrix, which is a critical step in pyruvate metabolism. An MPC inhibitor has shown promise as a novel therapeutic for MASH and HSC activation, but a mechanistic understanding of the direct effects of MPC inhibition on HSC activation is lacking. Methods: Stable lines of LX2 cells expressing short hairpin RNA against MPC2 were established and examined in a series of studies to assess HSC metabolism and activation. Mice with conditional, HSC-specific MPC2 deletion were generated and their phenotypes assessed in the context of diets that cause hepatic steatosis, injury, and early-stage fibrosis. Results: Genetic suppression of MPC activity markedly decreased expression of markers of HSC activation in vitro. MPC knockdown reduced the abundance of several intermediates of the tricarboxylic acid cycle and attenuated HSC activation by suppressing hypoxia inducible factor-1α signaling. Supplementing alpha-ketoglutarate to replenish the tricarboxylic acid cycle intermediates was sufficient to overcome the effects of MPC inhibition on hypoxia inducible factor-1α and HSC activation. On high-fat diets, mice with HSC-specific MPC deletion exhibited reduced circulating transaminases, numbers of HSCs, and hepatic expression of markers of HSC activation and inflammation compared with wild-type mice. Conclusions: These data suggest that MPC inhibition modulates HSC metabolism to attenuate activation and illuminate mechanisms by which MPC inhibitors could prove therapeutically beneficial for treating MASH.